Sexual behavior in later life unravelling the myth of the asexual old age. - Beleña, Aerra Mariel F.; Fornillos, Jholyan Francis S.; Gabrino, Anthony Niño M. (Aerra Marrie Beleña, 2013)
The myth of asexuality in old age remains pervasive especially in the context of Philippine social reality. This myth affects not only our portrayals of the older population but also research, policy agenda and clinical practice. However, the expressions of sexual behaviors among old individuals remain relatively unexplored. This research draws on qualitative data to unravel the myth of asexuality in old age. Research participants of this study were identified using purposive sampling. Interviews were conducted to generate data and then analyzed using thematic analysis. The results revealed that despite old age, participants still engage in a variety of sexual behaviors like kissing, hugging, flirting, caressing, dirty talking, pornography, genital fondling, masturbation, oral sex and sexual intercourse although individual differences in expressing these behaviors are affected by biopsychosocial factors confronting each participant. Even if high incidence of health problems and sexual dysfunctions are experienced in old age, participants still continue to express sexual behaviors in later life.